2017
DOI: 10.18203/2394-6040.ijcmph20173850
|View full text |Cite
|
Sign up to set email alerts
|

Source of previous anti-TB treatment for re-treatment TB cases registered under Revised National Tuberculosis Control Program in Pondicherry

Abstract: Background: Re-treatment TB cases are still a big challenge to National TB control programme. The objectives of the study were among retreatment TB cases, to study the source of previous anti-TB treatment, to find the time delays in initiating re-treatment and to find the risk factors for initiating retreatment under Revised National Tuberculosis Control Program (RNTCP) in Pondicherry.Methods: It was a cross sectional study. Source, date of completion or interruption of recent previous anti-TB treatment, misse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The reasons reported in our study for nonadherence of treatment are also reported in the other studies. 13,15,17,18 To confirm further the qualitative exploration of the reasons for retreatment category yielded similar responses.…”
Section: Sources Of Primary Anti-tb Treatment Karthikeyan Ganapathymentioning
confidence: 85%
See 1 more Smart Citation
“…The reasons reported in our study for nonadherence of treatment are also reported in the other studies. 13,15,17,18 To confirm further the qualitative exploration of the reasons for retreatment category yielded similar responses.…”
Section: Sources Of Primary Anti-tb Treatment Karthikeyan Ganapathymentioning
confidence: 85%
“…Majority of the people in Puducherry utilize the government health services; this was supported by the findings of study conducted by Prasad et al 14 Another study conducted in Puducherry has also reported similar finding. 15 The reason could be due to successful involvement of Medical Colleges through State Task Force Mechanism. But the study conducted in 2011 by Sachdeva et al has reported that more than half of the retreatment cases had treatment from non-RNTCP sources.…”
Section: Discussionmentioning
confidence: 99%